(untitled) (Journal of Engineering, 2019)
This study aimed to investigate the effect of total suspended solids (TSS) on the performance of a continuously operated dual-chamber microbial fuel cell (MFC) proceeded by primary clarifier to treat actual potato chips processing wastewater. The system was also tested in the absence of the primary clarifier and the results demonstrated a significant effect of TSS on the polarization curve of the MFC which was obtained by operating the graphite anodic electrode against Ag/AgCl reference electrode. The maximum observed power and current densities were decreased form 102.42 mW/m2 and 447.26 mA/m2 to 80.16 mW/m2 and 299.10 mA/m2, respectively due to the adverse effect of TSS. Also, the internal resistance increased from 40 to 70Ω.